PENINGKATAN PRODUKTIVITAS LINE STITCHING, PADA INDUSTRI ALAS KAKI DENGAN METODE OEE (OVERALL EQUIPMENT EFFECTIVENESS) STUDI KASUS DI PT PRATAMA ABADI INDUSTRI - Mashabai, Ismi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2017)
Productivity is an important point of the existence of the industry. PT Pratama Abadi Industri, which is one of Nike's footwear industry, need to increase their productivity. To achieve these objectives, this thesis using the method of Overall Equipment Effectiveness (OEE) in order to increase productivity, especially in the production process of stitching line. OEE value calculation results in line stitching for 2 years was 49.99% in the first year (SEP, 2014 s / d Agus 2015) <85.00% (world standard OEE values) and 50.81% in the second year (SEP 2015 s / d Agus 2016) <85.00% (world standard OEE values). The three variables that cause low OEE value is the loading time, the total pieces and defect.